BIG DATA AND PROFILING VERSUS GDPR - Domagała, Paweł Konrad (Człowiek w cyberprzestrzeni, 2020)
Nowadays, large data sets (Big Data) are used in telecommunications, marketing, transport, automotive, banking, tourism and many other areas. Nonetheless, aside of obvious opportunities for development, Big Data triggers numerous questions of a legal nature, including the proper implementation of the principles of data processing in large collections. There is also concern about the threat to the information autonomy of the individual or the need to give consent to profiling. Privacy is eroding mainly due to decisions taken by not always fully conscious and sovereign Internet users. The risks are increasingly recognised, stemming from the huge scale of data collection, tracking and profiling, security, transparency, and their incorrectness, discrimination and much wider supervision by the authorities of various countries. This paper examines the concept of Big Data and related profiling. Moreover, Big Data application and its possible limitations linked to personal data protection will be discussed. Accordingly, Big Data will be presented amidst the changes in personal data protection, once the General Data Protection Regulation (GPRD) has come into force.